Slapstick in the Wayang Kulit Arena: Gender Domination Practices Lead to Symbolic Violence - Saepudin, Asep; Fitriani, Tri Sat; Pambayun, Gandes (UIN Sunan Kudus, 2024)
This paper aims to explain the phenomenon of dagelan dalang and sinden in Yogyakarta's shadow puppet limbukan scene. Dagelan in Wayang is a humor/joke show to entertain the audience, usually done by dalang with sinden. For some people, dagelan is commonplace because it is generally presented in limbukan scenes for entertainment. However, dagelan in the limbukan section is not just entertainment but causes symbolic exploitation of sinden by the puppeteer with his various practices. Of course, this phenomenon is very paradoxical; on the one hand, the existence of sinden is significant because it supports the success of the shadow puppet show last night, but on the other hand, sinden becomes a victim of ridicule/laughter in a helpless condition because it is dominated and controlled by the puppeteer. The audience and group members even confirmed this dominance. In limbukan scenes, a sinden follows the puppeteer's instructions to sing a song while standing up and dancing. In addition, sinden is also the object of entertainment and even mockery of the mastermind with verbal and nonverbal language that causes discomfort. This is symbolic violence because sinden is a victim of entertainment exploitation. The conclusion shows that the extended exploitation of the mastermind against the sinden in the limbukan scene occurred because of the position of the sinden in a weak place in the ownership of capital compared to the mastermind. Sinden, however, is a part of the domination by the mastermind. On the contrary, puppeteers have various capital to become the dominant class with dominance and power. This leads to symbolic violence by the mastermind against Sinden and can even lead to mental violence.